Image Quantization in Psoriasis Using K-Mean Clustering - Nugroho, Arief Kelik (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Along with technology that is very fast image processing with high quality can be presented and displayed in many ways. The image has detailed information that can cause problems during processing. Image quantization is done as a preprocessing stage to reduce the number of colors in the image so that the resulting image approaches the original image. The purpose of this study is to group clusters of characteristics with the same image value.